2022
DOI: 10.3390/cancers14235863
|View full text |Cite
|
Sign up to set email alerts
|

Proton Beam Therapy for Pediatric Tumors of the Central Nervous System—Experiences of Clinical Outcome and Feasibility from the KiProReg Study

Abstract: As radiotherapy is an important part of the treatment in a variety of pediatric tumors of the central nervous system (CNS), proton beam therapy (PBT) plays an evolving role due to its potential benefits attributable to the unique dose distribution, with the possibility to deliver high doses to the target volume while sparing surrounding tissue. Children receiving PBT for an intracranial tumor between August 2013 and October 2017 were enrolled in the prospective registry study KiProReg. Patient’s clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The clinical protocol requires a planning MRI if the most recent diagnostic MRI is older than 30 days or if anatomical changes were likely in this period. For the 25 patients, who were part of a cohort of the KiProReg register study (DRKS00005363) [20], the acquisition of the planning scans was performed subsequent to the respective X-ray CT scan. In addition, the testing data set with 14 paediatric patients was used to assess the workflow with the most suitable parameter setting.…”
Section: Datamentioning
confidence: 99%
“…The clinical protocol requires a planning MRI if the most recent diagnostic MRI is older than 30 days or if anatomical changes were likely in this period. For the 25 patients, who were part of a cohort of the KiProReg register study (DRKS00005363) [20], the acquisition of the planning scans was performed subsequent to the respective X-ray CT scan. In addition, the testing data set with 14 paediatric patients was used to assess the workflow with the most suitable parameter setting.…”
Section: Datamentioning
confidence: 99%
“…Improvement in gross total resection (GTR) or subtotal resection (STR) of PBT has resulted in the targeted removal of the tumor and enhanced radiological treatment 6 . For example, proton beam treatment is one promising radiation therapy as it allows targeted dosing at high levels with reduced surrounding tissue damage 7 . Unfortunately, despite advancements, radiation therapy can cause hearing loss, impaired neurocognition, and alteration in neuroendocrine function, among other adverse events 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 For example, proton beam treatment is one promising radiation therapy as it allows targeted dosing at high levels with reduced surrounding tissue damage. 7 Unfortunately, despite advancements, radiation therapy can cause hearing loss, impaired neurocognition, and alteration in neuroendocrine function, among other adverse events. 8 , 9 , 10 The detrimental effect of radiotherapy in the modulation of BBB integrity was examined in immunocompetent and immunocompromised mice, and it was found that 12‐h irradiation in immunocompetent mice caused alteration of efflux transporter activity compared to immunocompromised mice indicating a role of proinflammatory molecules in BBB structural changes.…”
Section: Introductionmentioning
confidence: 99%